Analysis of Long Noncoding RNAs in Aila-Induced Non-Small Cell Lung Cancer Inhibition - Chen, Lin; Wu, Cui; Wang, Heming; Chen, Sinuo; Ma, Danhui; Tao, Ye; Wang, Xingye; Luan, Yanhe; Wang, Tiedong; Shi, Yan; Song, Guangqi; Zhao, Yicheng; et al. (Frontiers in Oncology, 2021)
Non-small cell lung cancer (NSCLC) has the highest morbidity and mortality among all carcinomas. However, it is difficult to diagnose in the early stage, and current therapeutic efficacy is not ideal. Although numerous studies have revealed that Ailanthone (Aila), a natural product, can inhibit multiple cancers by reducing cell proliferation and invasion and inducing apoptosis, the mechanism by which Aila represses NSCLC progression in a time-dependent manner remains unclear. In this study, we observed that most long noncoding RNAs (lncRNAs) were either notably up- or downregulated in NSCLC cells after treatment with Aila. Moreover, alterations in lncRNA expression induced by Aila were crucial for the initiation and metastasis of NSCLC. Furthermore, in our research, expression of DUXAP8 was significantly downregulated in NSCLC cells after treatment with Aila and regulated expression levels of EGR1. In conclusion, our findings demonstrate that Aila is a potent natural suppressor of NSCLC by modulating expression of DUXAP8 and EGR1.